'Recovery work' and 'magic' among long‐term mental health service‐users. Issue 2 (12th May 2013) - Laws, Jennifer
Abstract Based on an extended period of qualitative research with mental health service‐users in north‐east England, this article considers the various forms of 'magical work' and 'recovery work' that emerge in the lives of people living with severe mental health problems. Given the now sizeable body of literature which seeks to problematize traditional conceptual boundaries of work, the article asks to what extent these hidden and unusual work‐forms might also be considered legitimate members of the category. Rather than argue for the expansion of the construct to accommodate these activities, the paper attempts simply to problematize the extent to which so‐called 'mad' forms of work are irresolvably different to more conventional forms of occupation. In challenging notions of the psychiatric patient as inevitably inactive, new vocabularies for service‐user work are explored. Concluding remarks are also directed to recent policy debates concerning 'back‐to‐work' welfare reform for long‐term out of work service‐users.